Pengaruh Perubahan Tarif, Metode Perhitungan, Mekanisme Pembayaran Pajak, dan Sanksi Pajak terhadap Kepatuhan Wajib Pajak UMKM dengan Keadilan Pajak sebagai Variabel Moderasi di Kota Bangkalan - Wulandari, Maulia; Dawam, Aulia (Sosio e-Kons, 2024)
This research aims to examine the effect of changes in tariffs, calculation methods, tax payment mechanisms and tax sanctions on MSME taxpayer compliance with tax justice as a moderating variable in Bangkalan City. This research uses descriptive quantitative research, with data collection carried out directly from MSMEs. Data collection techniques include distributing questionnaires, documentation and observation. In this research, the technique used is the non-probability sampling technique. The sampling technique uses the convenience sampling technique. Simultaneously the results of the independent variables X1, X3, Meanwhile, variable X2 does not have a positive effect on variable Y because the sig value is greater than 0.05, which indicates a value that is not statistically significant.